Constructing (Il)Legitimate Democracy: Populism and Power Concentration in Newspaper Discourse on Venezuela - Ernesto Abalo (tripleC: Communication, Capitalism & Critique)
Despite scholarly consensus about the importance of the media for democracy, scant attention has been paid to what democracy means to journalistic discourse and how discourses on democracy are interrelated with legitimacy. The aim of this paper is to explore how (il)legitimate democracy is constructed in newspaper discourse. By using critical discourse analysis, this paper examines foreign news items about Venezuela, a country that under the presidency of Hugo Chávez has challenged the hegemonic global political and economic orders. The analysis section focuses on two main findings about the Venezuelan government: the constructions of populism and power concentration, which serve to mark deviance from what is perceived as legitimate democracy. This paper argues that a liberal perception of democracy constitutes a central framework for the construction of (il)legitimate democracy, which is revealed not least by news discourse’s focus on what is morally unacceptable political conduct according to liberal democratic norms. In this sense, such constructions serve to denounce potential governmental power abuses but also to legitimize the hegemonic economic and political orders.